Analysis of Community Satisfaction in Providing Public Services at the Tempe District Office, Wajo Regency - Aminah*, Sitti; Burhanuddin, Burhanuddin; Abidin, Fikri H.; Suciati, Suciati (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The success of providing public services is largely determined by the level of community satisfaction. Community satisfaction is achieved when service recipients receive services in accordance with what is needed and expected. The aim of this research is to determine and analyze the level of public satisfaction in the provision of public services at the Tempe District Office, Wajo Regency, as well as to analyze and describe the factors that are obstacles and supporters in the provision of public services at the Tempe District Office, Wajo Regency. This type of research is a qualitative case study type approach with data collection techniques through observation, in-depth interviews and documentation studies. The results of the research show that the analysis of community satisfaction in the implementation of public services at the Tempe District Office, Wajo Regency is based on indicators of elements of community satisfaction, namely requirements, systems, mechanisms, procedures, completion time, tariff costs, product specifications, types of services, competency of implementers, behavior of implementers, complaint handling, facilities and infrastructure can be categorized as not fully meeting community satisfaction and service recipients have not received services according to what is needed and expected. This can be seen in the uncertainty of the completion time for population administration services, as well as the lack of population data processing equipment. Apart from that, there is still a lack of socialization to the public regarding service requirements, so that it does not meet the expectations and satisfaction of service users.